The Human Novel Gene LNC-HC Inhibits Hepatocellular Carcinoma Cell Proliferation by Sequestering hsa-miR-183-5p - Xi Lan; Nan Wu; Litao Wu; Kai Qu; Ezra Kombo Osoro; Dongxian Guan; Xiaojuan Du; Bo Wang; Sifan Chen; Ji Miao; Juan Ren; Li Liu; et al. (Elsevier, 2020)
Hepatocellular carcinoma (HCC) is the most commonly diagnosed cancer and the leading cause of cancer mortality. Several lines of evidence have demonstrated the aberrant expression of long noncoding RNAs (lncRNAs) in carcinogenesis and their universal regulatory properties. A thorough understanding of lncRNA regulatory roles in HCC pathology would contribute to HCC prevention and treatment. In this study, we identified a novel human lncRNA, LNC-HC, with significantly reduced levels in hepatic tumors from patients with HCC. MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-dimethyltetrazolium bromide) assays as well as colony formation and wound healing experiments showed that LNC-HC significantly inhibited the proliferation of the HCC cell line Huh7. Xenograft transplantation of LNC-HC-overexpressing Huh7 cells in nude mice resulted in the production of smaller tumors. Mechanistically, LNC-HC inhibited the proliferation of HCC cells by directly interacting with hsa-miR-183-5p. LNC-HC rescued the expression of five tumor suppressors, including AKAP12, DYRK2, FOXN3, FOXO1, and LATS2, that were verified as target genes of hsa-miR-183-5p. Overall, human LNC-HC was identified as a novel tumor suppressor that could inhibit HCC cell proliferation in vitro and suppress tumor growth in vivo by competitively binding hsa-miR-183-5p as a competing endogenous RNA (ceRNA). These findings suggest that LNC-HC could be a biomarker of HCC and provide a novel therapeutic target for HCC treatment.